SIGNIFIKANSI KEGIATAN BANK SAMPAH DITINJAU DARI ASPEK KEUANGAN DI KELURAHAN PONDOK PINANG JAKARTA - Dila Angraini; Dea Annisa; Tri Utami (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2021)
There are many activities that can be carried out, such as waste processing. In Indonesia, waste management activities have been carried out in recent years. This is an alternative in controlling waste, and on the other hand it can be an additional income for the community. This study aims to analyze the activities of waste waste in terms of economic value. Can this activity be an alternative income for residents? In testing scientific action, namely a quantitative approach. The unit of analysis is the community who are members of the waste bank activities in the Pondok Pinang urban village, Jakarta. The technique of collecting data is distributing questionnaires. While the analysis technique uses linear regression. The fact of this research is that the activities of the waste bank explicitly generate income, namely in the form of savings. Mathematically, savings from waste management can explain income. In other words, the potential of this activity is enormous for income levels